Estudo sobre o livro-imagem: composição, leitura e criação - Setton, Luisa (2024)
This research aims to present reflections regarding the composition and reading of the wordless picturebooks, highlighting its implications of meaning and specificities. The study was based on the analysis of three wordless picturebook, namely, Praia-mar (2011), by Bernardo P. Carvalho, publisher Planeta Tangerina; Benedito (2014), by Josias Marinho, publisher Caramelo, and Mudar (2021), by Ana Ventura, publisher Patológico. We searched to understand the points of rapprochement between wordless picturebooks and picturebooks and the main differences between these books from the view of reading and enjoyment. Furthermore, the analysis intends to relate specific aspects of the wordless picturebook with concepts from reception aesthetics. This approach sought to contribute to the debate about the literary dimension attributed to essentially visual narratives. The dissertation is bibliographic and qualitative and is divided into three chapters. The first one addressed some relationships between the wordless picturebook and the picturebook, highlighting specificities of the composition of the wordless picturebook, using, above all, concepts from Nikolajeva and Scott (2011), Linden (2011; 2015), Lee (2012), Lartitegui (2023), Bosch (2015) and Arizpe (2014). The second chapter analysed three picture books and their implications of meaning. The third chapter reflected on concepts of reception aesthetics that are close to the reading of image books based on the contributions of Iser (1979), Jauss (1979) and Compagnon (2003)